Investigating the level of students' awareness and perception on the unemployment issue among graduates and their preparation for the job market : A case study at Faculty of Information Technology & Quantitatve Sciences, UiTM Shah Alam / Norhisalmim Mohamad - Mohamad, Norhisalmim (Faculty of Computer and Mathematical Sciences, 2004)
This study is an attempt to identify the awareness of the unemployment issue among graduates across the final year degree and final year diploma students at Universiti Teknologi MARA (UiTM) Shah Alam. The main purpose of this study is to identify the level of student's awareness on the unemployment issues among graduates and their preparation for the job market. The other objectives are to compare the students' perceptions on the unemployment issues among graduates with demographic profiles. A stratified random sampling has been used to determine the sample size. The data was collected by distributing the questionnaire to the respondents. The computer packages used for this analysis were SPSS and Microsoft Excel. The test statistics used were the Descriptive Test, Normahty Test, T-test and ANO VA Test. The result found that most of the respondents were aware about the unemployment issues and there was significant difference in the perceptions on the unemployment issues between the levels of education and among age group. It also found that most of the students agreed about the factors that contributed to imemployment. While looking into the students' self-evaluation of employability skills, it was found that both male and female students were 'good' for all the mentioned skills except for "Strong leadership skill" and "Must be effective team player"